Bmi-1 overexpression as an efficient prognostic marker in patients with nonsmall cell lung cancer. Issue 26 (June 2017) - Zhang, Xiaojun; Tian, Tian; Sun, Wei; Liu, Changting; Fang, Xiangqun
Abstract: Background: The prognostic effect of B-cell-specific Moloney leukemia virus insertion site 1 (Bmi-1) in patients with nonsmall cell lung cancer (NSCLC) remains controversial. We thus performed a meta-analysis to reveal the correlation between Bmi-1 with clinical features and overall survival (OS) in NSCLC. Methods: Relevant studies were searched through PubMed, Embase, and Web of Science. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) as well as odds ratios (ORs) and 95% CIs were calculated by using STATA version 12.0. Results: Fourteen studies consisting of 1323 patients were included for quantitative analysis. The results showed that Bmi-1 was significantly associated with tumor size (n = 7, OR = 1.79, 95% CI = 1.19–2.71, P  = .005, fixed effect), poor differentiation (OR = 1.61, 95% CI = 1.11–2.33, P  = .011, fixed effect), and distant metastasis (n = 4, OR = 4.69, 95% CI = 1.52–14.41, P  = .007, fixed effect). In addition, high Bmi-1 expression also predicted poor OS (HR = 1.62, 95% CI = 1.14–2.3, P  < .001). There was no significant publication bias for any of the analyses. Conclusion: In conclusion, Bmi-1 overexpression was correlated with tumor size, poor differentiation, distant metastasis, and worse OS in NSCLC. Therefore, Bmi-1 could be recommended as an efficient prognostic marker for NSCLC.